Forms of Violation of Law of the Republic of Indonesia Number 24 of 2009 Concerning the Use of Indonesian as Geographical Names in Indonesia - Fauzi, Aziz; Prima Sintasari, Diardana (International Proceedings of Nusantara Raya, 2023)
The use of Indonesian by the general public today is still very inappropriate. The phenomenon of language use in public spaces which includes many spelling errors, vocabulary and Indonesian structure. Good and correct use of Indonesian is often hindered by the presence of other languages. Researchers will try to explain the form of non-compliance from the mandate of Law of the Republic of Indonesia No. 24 of 2019 concerning "Flag, Language, and National Emblem, as well as the National Anthem". The method used, namely qualitative methods, is descriptive. The sources taken from this study amounted to 5 places with the use of foreign languages and inappropriate words. The results of this study show that there are violations of laws regarding language caused by several things, including incorrect grammar, improper grammar in certain circumstances, using foreign terms even though there are equivalents in Indonesian, translating foreign languages at will. So the names of institutions, businesses, shops, areas, buildings, etc. often use foreign languages exclusively because of socioeconomic and commercial points of view.